2008
DOI: 10.1039/b800264a
|View full text |Cite
|
Sign up to set email alerts
|

Facile approach to prepare loose-packed NiO nano-flakes materials for supercapacitors

Abstract: The nickel oxide nano-flakes materials prepared by a facile approach maintain high power density at high rates of discharge and have excellent cycle life, suggesting their potential application in supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
179
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(186 citation statements)
references
References 25 publications
6
179
0
1
Order By: Relevance
“…The prepared nano-NiO materials include nanocolumns, nanosheets, nanoflakes, nanorings, hierarchical porous nanoflowers, nano/microspheres, porous nanowall arrays as well as hollow nanospheres. [435][436][437][438][439][440][441] In particular, the porous structure of hollow nanospheres can act as an ''ion reservoir'', leading to not only high surface area but also better mass transportation, ensuring steady supply of ions for Faradic reactions at high current densities. 442 Regarding the synthesis, the template-based method is the most common method for preparing NiO hollow nanospheres.…”
Section: à2mentioning
confidence: 99%
“…The prepared nano-NiO materials include nanocolumns, nanosheets, nanoflakes, nanorings, hierarchical porous nanoflowers, nano/microspheres, porous nanowall arrays as well as hollow nanospheres. [435][436][437][438][439][440][441] In particular, the porous structure of hollow nanospheres can act as an ''ion reservoir'', leading to not only high surface area but also better mass transportation, ensuring steady supply of ions for Faradic reactions at high current densities. 442 Regarding the synthesis, the template-based method is the most common method for preparing NiO hollow nanospheres.…”
Section: à2mentioning
confidence: 99%
“…Among such oxides, NiO is of particular interest owing to its high theoretical specific capacitance of 2573 F/g [22,23], high chemical/thermal stability, ready availability, environmentally benign nature and lower cost as compared to the state-of-the-art supercapacitor material RuO 2 [24,25]. There have been a variety of reports of the synthesis of different NiO nanostructures including porous nano/microspheres [26], nanoflowers [27], nanosheets [28], and nanofibers [29]. It has been shown that the electrochemical performance of NiO nanocrystals largely depends on its microstructure, surface area, and the presence of dopants [30][31][32][33][34][35], suggesting that the development of controlled syntheses of NiO nanostructures with the desired features, e.g., high electronic conductivity, low diffusion resistance to protons/cations, and high electroactive area is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…The porous NiO nanocolumns also show higher specific capacitance (390 F/g) at a discharge current of 5 A/g than that of nanoslices and nanoplates (285 and 176 F/g, respectively). Although there are reports in the literature of the synthesis of NiO nanocrystals with higher specific capacitances, e.g., porous NiO spheres [26] with specific capacitances > 525 F/g at a discharge current of 4 A/g and NiO nanoflowers [27] with specific capacitances of ~800 F/g at a discharge current of 10 mA, the current work demonstrates a clear process-related trend in the specific capacitance of the resulting electrode materials, which may provide an additional strategy to improve the performance of supercapacitors made of various materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that electrode material is one of the dominating factors that influence the performance of the ECs [3,4]. At present, three different types of supercapacitors are commonly described in literature, depending on the nature of the active material used, carbon materials [5][6][7], conducting polymers [8][9][10], and metal-oxides [11][12][13]. Carbon materials are useful in wide application due to its good conductivity, low cost, and high surface area.…”
Section: Introductionmentioning
confidence: 99%